Elevated ALT/AST ratio as a marker for NAFLD risk and severity: insights from a cross-sectional analysis in the United States - Xuan, Yanyan; Wu, Dingting; Zhang, Qin; Yu, Zhiqiang; Yu, Jingbo; Zhou, Dongdong (Frontiers in Endocrinology, 2024)
The prevalence and incidence of Nonalcoholic fatty liver disease (NAFLD) are increasing worldwide, and NAFLD has emerged as a prominent global health concern. The link between serum alanine aminotransferase (ALT) to aspartate aminotransferase (AST) ratio and NAFLD remains unclear. This study investigated the association between the ALT/AST ratio and NAFLD prevalence, including liver steatosis and fibrosis levels in the population.: We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) 2017-2018, including 4753 participants. Subgroup analyses, stratified by age， gender, and body mass index (BMI), were performed, along with adjusted multivariable logistic regression analyses to evaluate the relationship between ALT/AST levels and the likelihood of NAFLD, liver steatosis, and hepatic fibrosis stage. A generalized additive model examined the non-linear relationship between ALT/AST and the probability of developing NAFLD.Results: Among 4753 participants, 1508 (31.73%) were diagnosed with NAFLD.Significant positive correlations between ALT/AST and NAFLD risk were found across all models. In addition, the subgroup analysis by gender, age, and BMI suggested that ALT/AST showed a positive correlation with NAFLD. The ALT/AST ratio was positively correlated with the degree of liver steatosis and liver fibrosis. The correlation between ALT/AST and the incidence of NAFLD showed a non-linear pattern. In women, the non-linear trend is particularly evident, showing an inverted U-shaped curve with an inflection point of 1.302. A receiver operating characteristic (ROC) analysis showed that the predictive value of ALT/AST for NAFLD was better than that of traditional liver enzyme parameters.A higher ALT/AST ratio was independently associated with a significantly higher risk of NAFLD and liver fibrosis within American cohorts. This link is robust among females, children, and adolescents. ALT/AST ratio can be used as a simple and effective noninvasive biomarker to identify individuals with high risk of NAFLD.